PREVALENCE OF HEPATITIS E VIRUS (HEV) ANTIBODY IN PREGNANT WOMEN OF KARACHI - SHAMS, RABIA; KHERO, RAZIA BAHADUR; AHMED, TOUSEEF; Hafiz, Amtul (Journal of Ayub Medical College Abbottabad, 2001)
Background: This study was aimed at determining the prevalence of HEV in Karachi. Methods: Prevalence of hepatitis | antibody in pregnant women was carried out in 65 pregnant women. They had history of acute viral hepatitis while 15 control pregnant women were included having no history of jaundice. Results: The statistical outcome of the present study indicates prevalence of HEV as 57% in pregnant women with jaundice. Majority of the patients (85%) were from lower socio-economic strata., with mean age of 25 years. All these patients had hemoglobin less than 10gm%. The mean ALT level in HEV positive cases was 452 IU/L over a range of 102-5328. It was also observed that HEV affected more women in the last trimester (62%) and in primigravida (67%). It was observed that it was more common in last trimester and in primigravida. Majority of the patients (85%) were from lower socio-economic strata. Conclusions: The findings of the present study proved the presence of HEV in pregnant women and confirmed that HEV is endemic in Karachi. The study confirms that it occurs in last trimester and in young adult.